Coupling of strain, stress, and oxygen non-stoichiometry in thin film Pr0.1Ce0.9O2−δ. Issue 36 (7th September 2016) - Sheth, J.; Chen, D.; Kim, J. J.; Bowman, W. J.; Crozier, P. A.; Tuller, H. L.; Misture, S. T.; Zdzieszynski, S.; Sheldon, B. W.; Bishop, S. R.
Abstract : Stress and strain evolution due to chemical expansion in Pr doped ceria thin films supported on two different substrates were investigated by employing in situ characterization techniques. Abstract : Stress and strain in thin films of Pr0.1 Ce0.9 O2− δ, supported on yttria stabilized zirconia (YSZ) and sapphire substrates, induced by large deviations from oxygen stoichiometry ( δ = 0) were investigated by in situ high temperature X-ray diffraction and wafer curvature studies. The measured stresses and strains were correlated with change in δ, measured in situ using optical transmission spectroscopy of defect centers in the films and compared with prior chemical capacitance studies. The coefficient of chemical expansion and elastic modulus values for the films were found to be 18% less than, and 16% greater than in the bulk, respectively. Irreproducible stress and strain during cycling on YSZ substrates was observed and related to microstructural changes as observed by TEM. The enthalpy of defect formation was found to be similar for films supported on sapphire and YSZ, and appeared to decrease with tensile stress, and increase with compressive stress. Larger stresses observed for YSZ supported films as compared to sapphire supported films were found and accounted for by the difference in film orientations.